How Does Emotional Intelligence, Learning Motivation and Learning Independence Affect Students' Critical Thinking Skills in Economics Subjects? - Muhammad Hasan; Thamrin Tahir; Nur Arisah; Muhammad Ilyas Thamrin Tahir; Marhawati Marhawati (Universitas Muhammadiyah Mataram, 2024)
Students must possess critical thinking abilities to succeed in the 21st century. Numerous factors influence the development of economics students' critical thinking abilities. This study aims to investigate the impact of emotional intelligence, learning motivation, and learning independence on students' critical thinking abilities in economics courses. This study employs a quantitative research methodology with a quantitative descriptive approach. The data in this study were collected using a questionnaire with closed questions on a Likert scale. Data was gathered from 630 respondents from the South Sulawesi Province of Indonesia and further analysed using SEM (Structural Equation Modelling). According to the findings of this study, emotional intelligence, learning motivation, and learning independence substantially impact critical thinking abilities. This study provides two main contributions. First, this study provides a theoretical contribution to the development of constructivist learning theory by including the importance of a combination of emotional, motivational, and independence factors in economic learning. Second, this study provides a practical contribution in the development of methods, media, and learning resources that are oriented towards students' critical thinking skills in economic learning.